Արեւելագիտության մոռացված երախտավոր Գ. Կեռի նամակը «Հայոց եպիսկոպոսին» - Հարություն Ժամկոչյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Керъ Г. Я. 1692 -1740 - первый в России ориенталист, уроженец Германии, изучал восточные языки в Галле. Керъ издал в Лейпциге “ Dissertatio de Saracenis, hagarenis et Mauris “ (1723 ); Monarchiae asiatico-saracenicae status, quails VIII et IX post. chr.natum saeculo fUit etc.” (1724 ); Monarchiae Mongoloindici vel Mongolis Magni Aurenz Szeb numisma etc.” (1725). Within the formation of my plan-works my attention was attracted to a European Armenian community with a letter, which nobody had read it. The author of this letter was a German orientalist G. Ya. Kehr (1692-1740 ), which in 1732 by the invitation of vice cansler Ostermann came to Saint- Peterburg.
Keywords: Biography; Auxiliary Sciences of History; Philology; Linguistics; Language and Literature; History of Scholarship; The Humanities